2006
DOI: 10.1183/09031936.06.00105904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hBD-3 in respiratory tract and serum: the increase in pneumonia

Abstract: Human b-defensin (hBD)-3, a 45 amino acid antimicrobial peptide, was originally isolated from human skin. hBD-3 mRNA has also been detected in the airways by RT-PCR. While hBD-3 may be involved in antimicrobial defences within the respiratory tract, the presence of hBD-3 peptide in the respiratory system has not yet been confirmed.The antimicrobial activity of the synthesised hBD-3 peptide was measured by a radial diffusion assay and a colony count assay. The present authors confirmed the presence of hBD-3 pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
1
36
2
1
Order By: Relevance
“…Previously we have shown that K. pneumoniae CPS mediates resistance to different antimicrobial peptides, including hBD1 (8,45). However, in those studies, the sensitivities of K. pneumoniae to hBD2 and hBD3, whose levels increase in the lung during pneumonia, were not tested (29,33). Survival assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we have shown that K. pneumoniae CPS mediates resistance to different antimicrobial peptides, including hBD1 (8,45). However, in those studies, the sensitivities of K. pneumoniae to hBD2 and hBD3, whose levels increase in the lung during pneumonia, were not tested (29,33). Survival assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hBD2 and hBD3 play an important role in host defense as inducible components of the epithelial barrier. Indeed, hBD2 and hBD3 levels increase severalfold in the lung during pneumonia (29,33). The importance of BDs in lung defense has been established by the use of knockout mice.…”
mentioning
confidence: 99%
“…[13][14][15] Unlike other HBDs, HBD-3 is a salt-insensitive defensin with broad antimicrobial activity against multidrug-resistant nosocomial strains. 12,16,17 Concerning vaginal innate immunity, little is known about the mechanism by which epithelial cells are activated by the pathogens, receptors, and mediators involved in the immune response. A previous study reported HBD-2 expression and NF-κB activation in vaginal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human β-defensin-3 (hBD3) was first isolated from human skin (7) and its expression was detected in many tissues, including airway epithelial cells (8,9). In contrast to other defensin isoforms, the prominent features of hBD3 antimicrobial activity are its salt-independency and its broad antimicrobial spectrum (7, 10, 11).…”
mentioning
confidence: 99%
“…In the defensin family, there are α-defensin and β-defensin subfamilies, which conserve three specific disulfide pairings. These are produced by leukocytes and various types of epithelial cells constitutively, or in response to microbial signals and inflammatory cytokines (4-6).Human β-defensin-3 (hBD3) was first isolated from human skin (7) and its expression was detected in many tissues, including airway epithelial cells (8,9). In contrast to other defensin isoforms, the prominent features of hBD3 antimicrobial activity are its salt-independency and its broad antimicrobial spectrum (7, 10, 11).…”
mentioning
confidence: 99%